Ethnic identification of the Kazakhs by subclads of the Y-chromosome haplogroup C2 - A. M. Tyurin (Nomadic Civilization: Historical Research, 2025)
Y-chromosome haplogroups (transmitted through the male line) C2, O and D are called Mongolian. Among the Kazakhs of Kazakhstan, 40–52 % are carriers of haplogroup C2, 8 % are carriers of O and up to 1 % are carriers of D. In total, Mongolian haplogroups are 49–60 %. In this indicator, Kazakhs are practically no different from Kalmyks. Four subclades have been identified in haplogroup C2: C2a1a2a-M48(×M504) «Kalmyks» (dominant in frequency among Kalmyks), C2a1a2b-M48(M504) «Kalmaks» (dominant among Kalmaks), C2b-F1067 «Khalkha» (dominant among the Khalkha Mongols) and C2-Y10418 «Avars» (not ethnically identified). Kalmyks and Kalmaks (Dzungars) are Oirat Mongols. Such distribution of subclade frequencies allows ethnic identification of Kazakhs, carriers of haplogroup C2. 21 arrays (number of tested — 6484) of population genetics data characterizing Kazakhs by regions of residence, zhuzes and clans were considered. Kalmaks made a decisive contribution to the ethnogenesis of Kazakhs of the Senior zhuz, Kalmyks — to the Junior zhuz. Their contribution to the genetic portrait of the clans of the Middle zhuz is differentiated. There were no Khalkha Mongols in the territory of formation of the Kazakh ethnic group (the eastern part of the Jochi ulus and the northern part of the Chigatai ulus). The frequencies of the Khalkha subclade among them are at the level of its frequencies among Kalmyks. The exception is the Kazakhs of the Turkestan region. They have 20 % of its carriers. The main mechanism of formation of the Kazakh ethnic group is social. Initially, the Kazakh hordes were formed in the same way as in Eastern Europe. From individuals who came from different social systems. Later, individual Oirat clans moved from the rigid feudal structure of the Kalmyk and Dzungar Khanates to the Kazakh hordes. The second most important mechanism is the creation of the shezhire as a national myth of the Kazakhs